Unhappiness Intensifies the Avoidance of Frequent Losses While Happiness Overcomes It - Yechiam, Eldad; Telpaz, Ariel; Krupenia, Stas; Rafaeli, Anat (Frontiers in Psychology, 2016)
The implication of spontaneous and induced unhappiness to people’s decision style is examined. It is postulated that unhappy individuals have a greater tendency to avoid frequent losses because these can have depleting effects, and unhappy individuals are more sensitive to such effects. This is evaluated in Study 1 by using an annoying customer call manipulation to induce negative affect; and by examining the effect of this manipulation on choices in an experiential decision task (the Iowa Gambling task). In Study 2 we examined the association between self-reported (un)happiness and choices on the same decision task. In Study 1 the induction of negative affect led to avoidance of choice alternatives with frequent losses, compared to those yielding rarer but larger losses. Specifically, this pertained to the advantageous alternatives with frequent versus non-frequent losses. In Study 2 unhappiness was similarly associated with less exposure to frequent losses; while extreme high happiness was associated with no tendency to avoid frequent losses when these were part of an advantageous alternative. The findings clarify the role of happiness in decision making processes by indicating that unhappiness induces sensitivity to the frequency rather than to the total effect of negative events.